Increased Risk of Deep Vein Thrombosis and Pulmonary Thromboembolism in Patients With Organophosphate Intoxication: A Nationwide Prospective Cohort Study - Lim, Yun-Ping; Lin, Cheng-Li; Hung, Dong-Zong; Ma, Wei-Chih; Lin, Yen-Ning; Kao, Chia-Hung (Medicine (Baltimore), 2015)
Organophosphate (OP) poisoning is a critical cause of morbidity and mortality worldwide. We conducted a nationwide longitudinal cohort study to investigate the development of deep vein thrombosis (DVT) and pulmonary thromboembolism (PTE) among patients admitted with OP intoxication.We identified patients with OP intoxication by using the Taiwan National Health Insurance Research Database and enrolled 9223 patients who were hospitalized for OP intoxication between 2000 and 2011. OP intoxication was diagnosed based on a clinical assessment and serum acetylcholinesterase levels at the time of hospital admission. Each patient in the OP intoxication cohort was randomly frequency matched with 4 patients without OP intoxication based on their age, sex, and index year (36,892 patients as control cohort), and all patients were observed from the index date until the appearance of a DVT or a PTE event, or until December 31, 2011. We analyzed the risks of DVT and PTE by using Cox proportional hazards regression models that included the demographic variables of sex, age, and comorbidities (eg, hypertension, diabetes, cerebral vascular disease, heart failure, all cancer types, and lower leg fracture or surgery).The results revealed a significantly increased risk of developing DVT among patients with OP poisoning (adjusted hazard ratio [HR] = 1.55; 95% confidence interval [CI] = 1.03-2.34) but not PTE (adjusted HR = 1.44; 95% CI = 0.83-2.52). Among the patients without comorbidities, the OP poisoning patients compared with controls had a higher adjusted HR of 2.12 (95% CI = 1.21-3.71) for DVT.The results of this nationwide cohort study indicate that the risk of developing DVT is markedly higher in patients with OP intoxication compared with that of the general population.